Parental Readiness in Child Rearing in the Digital Era - Widiastuti, Reski Yulina; Nanik Yuliati (Universitas Pendidikan Ganesha, 2025)
The rapid development of digital technology today offers various conveniences in human life, including in parenting practices. However, the lack of parental knowledge and skills in guiding children in the digital era can have negative impacts on children’s growth and development, especially in terms of excessive and unmonitored technology use. This study aims to analyze parents' readiness in applying adaptive and wise parenting patterns in the digital age. The research employed a quantitative survey approach, with data collected through an online questionnaire via Google Form. The research instrument consisted of 30 statements divided into 4 indicators, measured using a Likert scale. The study involved 99 parents selected using a simple random sampling technique. Data were analyzed descriptively to obtain an overview of parents’ readiness in digital parenting. The results showed that the level of parental readiness was in the